Multi Resolution Analysis Compared Savitzky-Golay and Moving Average Filter by Noise Reduction - Soto-Gomez, J; San Juan-Urrutia, E; Canete-Arratia, L; Adasme-Soto, P (Institute of Electrical and Electronics Engineers Inc., 2020)
The aim of this paper is to offer an alternative signal analysis using Multiresolution Analysis (MRA), with the practical purpose of analyzing its performance in reducing the noise components. In a first part, a brief theoretical basis is shown for the Wavelets theory for signal analysis. Subsequently, simulations are carried out to reduce the noise through the multiresolution analysis of the Discrete Wavelet Transform and the they are compared with the results obtained through typical filters, such as Savitzky-Golay and Moving Average Filter. © 2020 IEEE.